Factor Influencing Willingness to Pay for Prediabetes Screening and Prevention Program: A Systematic Review - Rochmanov, Janne; Kristina, Susi Ari; Yasin, Nanang Munif (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: IDF, or The International Diabetes Federation predicts that by 2045, there will be 783 million adults (12,2%) with diabetes globally, up from 540 million (10,5%) in 2021 projects that by 2045, there will be 783 million adults (12,2%) with diabetes globally, up from 540 million (10,5%) in 2021. Research has shown that lifestyle modifications, such as changes in diet and exercise, can significantly reduce the chance that prediabetes patients will get diabetes.Objectives: The aim of this systematic review was to examine the factor influencing willingness to pay (WTP) for prediabetes screening and prevention programs.Methods: Between October and December 2023, relevant keywords were used to search Scopus, PubMed, Sage, and Web Science for articles published between 2006 and 2023. This provided the necessary information. The Quality assessment of the studies was assessed using JBI for Cross–Sectional studies.Results: Finally, a total of eight studies were selected for review. Over 90% of the participants were men, and most had experience as health workers. Overall, respondents accepted it well with a positive prevalence of high willingness to pay, namely more than 78.9%. The most frequently used method for measuring WTP was CVM (25%) and DCM (25%).Conclusion: Despite the fact that some people would prefer to pay more, the results demonstrated that WTP was comparatively high when screening tests and preventative were provided for free or at a reasonable cost. It is recommended to increase people's awareness and motivation for lay people with diabetes.